A scoping review of social determinants of health curricula in post-graduate medical education - Hunter, Kimberly Anne; Thomson, Ben (Canadian Medical Education Journal, 2019)
Social determinants of health are responsible for 50% of ill health. The Royal College of Physicians and Surgeons of Canada CanMEDS role of “physician advocate” requires physicians to attain competency in this particular domain, but physician trainees feel this is not well covered in their training programs. This study performed a scoping review of social determinants of health curricula that had been described, implemented and evaluated in post-graduate medical education. A search using MEDLINE(OvidSP) database, with search terms “residency,” ”curriculum,” and “social determinants” with no age, language, and publication date restrictions was done.Researchers identified a total of 12 studies, all from the United States, in internal medicine (n=4), pediatrics (n=4), family medicine (n=2), or multiple (n=2) residency programs. Most curricula (n=8, 67%), were longitudinal, and most contained both patient or community exposure (n=11, 92%) and/or classroom-based components (n=10, 83%). Most (78%) curricula improved participant related outcomes, including exam performance, awareness regarding personal practice, confidence, improved screening for social determinants of health and referral to support services. Program specific outcomes were frequently positive (50%) and included resident satisfaction and high course evaluation scores, high representation of resident and faculty from minority groups, applicability of training to underserviced populations, and improved engagement of marginalized community members. When evaluated, academic outcomes were always positive, and included acceptance of scholarly projects to national conferences, publication of research work, grants earned to support health projects, local or national awards for leadership and community engagement, and curriculum graduates later pursuing related Masters degrees and/or establishing medical practices in underserved areas. Only one study reported a patient-related outcome, with advice provided by health care providers considered by patients to be helpful. Researchers used these results to design recommendations for creation of a post-graduate curriculum to address social determinants of health were provided.